EVALUATING THE IMPACT OF USING GITHUB COPILOT BY COMPUTER SCIENCE STUDENTS IN UNIVERSITI MALAYSIA SARAWAK - Etheldritha, Lim Han Ching (Universiti Malaysia Sarawak, (UNIMAS), 2023)
Programming or coding is an important skill that has to be learn by computer science students. There has been a couple of coding assistance tools in the market. The latest one is Artificial Intelligent driven code completion tools, such as GitHub Copilot that help students write code with just a simple natural language command in the form of comment. This tool is a great help for programmers as it fastens the time taken to write a program. However, it is unknown whether this tool can be a great learning tool for students that are still learning and mastering programming skill and languages. This research is done to evaluate the impact and acceptance of using GitHub Copilot among computer science students in Universiti Malaysia Sarawak and to find out the parameters that can be used to evaluate students’ efficiency in coding a program. To do this research, a controlled experiment involving a selective group of students who used both GitHub Copilot and conventional programming methods to complete a programming task and then questionnaires will be distributed to the group of students. The questionnaires contain question to find out the students’ opinion of the tools and how well they are accepting it using the Unified Theory of Acceptance and Use of Technology (UTAUT). After the students answer the survey, the result will be discussed and analyse. Overall, the result of the evaluation reveals that GitHub Copilot significantly improved the productivity of computer science students. The tool shortens the code-writing process, reducing development time and minimizing the likelihood of syntax errors. Additionally, GitHub Copilot enhanced code quality by suggesting relevant and accurate code snippets. However, some students consider the usage of the tool as cheating and plagiarising. The user satisfaction may vary depending on individual preferences and experiences. Therefore, careful monitoring and guidance are necessary to ensure that students strike a balance between utilizing the tool and developing their own coding expertise.